Clinical outcomes of arthroscopic modified suture augmentation versus InternalBrace™ reconstruction in the treatment of chronic ankle instability - Zifeng Wu; Piao Xie; Shuoshuo Gu; Dahai Hu; Jinsong Hong; Xiaofei Zheng; Jieruo Li; Huige Hou (BMC Musculoskeletal Disorders)
Abstract Background At present, the modified suture augmentation (MSA) repair and the InternalBrace™ (IB) reconstruction techniques are commonly used for the treatment of chronic ankle instability (CAI). This study aimed to evaluate and compare the clinical efficacy of the MSA repair and IB reconstruction techniques, providing a reference for clinical practice. Methods After propensity score matching, 50 patients with CAI between May 2021 and May 2022 were included in this retrospective study. Of these, 26 underwent IB reconstruction surgery and 24 underwent MSA repair surgery. The American Orthopedic Foot and Ankle Society (AOFAS) scores, visual analog scale (VAS) scores, anterior drawer tests, and patient satisfaction were used for clinical efficacy evaluation. Results The postoperative AOFAS scores in the MSA group (88.8 ± 3.0) were significantly higher than those in the IB group (84.3 ± 5.4, P = 0.001). However, the patient satisfaction scores in the IB group (7.3 ± 0.8) were higher than those in the MSA group (6.7 ± 0.8, P = 0.02). There were no significant differences between the two groups in the anterior drawer test results and VAS scores (P < 0.05). In addition, regarding postoperative complications, only one patient (4.2%) in the MSA group had joint laxity. Conclusions MSA repair was superior to IB reconstruction in terms of AOFAS scores. However, IB reconstruction was superior in terms of patient satisfaction. These findings highlight the potential of MSA repair and IB reconstruction techniques for the treatment of CAI.